KEPASTIAN HUKUM PENATAAN RUANG WILAYAH SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG PENATAAN RUANG - Sulistyawati, Ni Putu Yunika; Sang Ayu Made Ary Kusumawardhani; Ni Luh Sutariani (Kerta Dyatmika, 2024)
Law Number 26 of 2007 concerning Spatial Planning regulates the structure and spatial patterns of a region as the foundation for sustainable development. Spatial structure refers to the arrangement of settlement centers and the infrastructure and facilities network that support socio-economic activities, while spatial patterns refer to the distribution of land use for protected areas and cultivation areas. This study aims to examine the implementation of spatial planning policy in Indonesia and the legal certainty of spatial planning following the enactment of Law Number 26 of 2007. The research employs a normative legal method with a statutory and policy analysis approach. The findings reveal that the implementation of spatial planning policy is carried out by both central and regional governments, involving community participation as a critical element in achieving spatial planning objectives namely, the realization of safe, comfortable, productive, and sustainable national space. Legal certainty in spatial planning serves as an indicator of professionalism and government credibility, and is essential in the formulation of development policies. These policies must ultimately be codified into the legal system to possess binding legal force and guarantee legal certainty. The study concludes that, to ensure clean governance and good public administration, legal development must uphold procedural fairness, public accountability, and responsiveness to public aspirations, all of which must be supported by a legal system that guarantees certainty in spatial planning.